2021
DOI: 10.1016/j.tibtech.2021.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Multiproduct Microalgae Biorefineries Mediated by Ionic Liquids

Abstract: Hydrophobic components can be extracted from intact microalgae.Separation of hydrophilic and hydrophobic components is feasible with intact and disrupted microalgae.Extraction can be performed without compromising the proteins structural integrity.Multiproduct microalgae biorefining is a feasible approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 96 publications
(157 reference statements)
0
9
0
Order By: Relevance
“…In this context, C. saccharophila is a strain that has potential for use in biorefinery applications, facilitating the circular bioeconomy. However, a multiproduct strategy based on the biorefinery concept for the sequential extraction of numerous high‐value renewables (e.g., proteins, lipids, pigments, and carbohydrates) is yet to be developed 68 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, C. saccharophila is a strain that has potential for use in biorefinery applications, facilitating the circular bioeconomy. However, a multiproduct strategy based on the biorefinery concept for the sequential extraction of numerous high‐value renewables (e.g., proteins, lipids, pigments, and carbohydrates) is yet to be developed 68 …”
Section: Resultsmentioning
confidence: 99%
“…However, a multiproduct strategy based on the biorefinery concept for the sequential extraction of numerous high-value renewables (e.g., proteins, lipids, pigments, and carbohydrates) is yet to be developed. 68…”
Section: Biochemical Profiling and Analysismentioning
confidence: 99%
“…The most frequently used cations are imidazolium-based ions due to their stable chemical property and availability. 532 The effect of length of alkyl side-chain on the extraction efficiency was discussed in study of Sorokina et al 533 This study has shown that under 65 533 This result indicated that the ILs with larger HB acceptor were more effective in the extraction process.…”
Section: Biofuel Precursor Extraction From Microalgaementioning
confidence: 98%
“…Ionic liquids (ILs) are characterized by high design flexibility and tunability and a wide range of polarity and capacity to solubilize a wide variety of organic and inorganic compounds. , In addition, their low volatility eliminates a major concern for contamination, and a large number of ILs are already available with low toxicity, low cost, and high biodegradability. It is preferred, however, to reuse the IL after regeneration to avoid the presence of IL in the waste and to minimize costs for the process.…”
Section: Introductionmentioning
confidence: 99%